PENGUATAN ETIKA PROFESI GURU MELALUI KEBIJAKAN SATUAN PENDIDIKAN DI ERA DIGITAL - Muhtar, Aprilia Kartika; Ariendra, Reva Dwi; Azahro, Navisa; Khasanah, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology in education has significantly transformed learning methods and interactions between teachers and students, while also creating new challenges in the implementation of teacher professional ethics. Therefore, strengthening teacher professional ethics is essential to maintain professionalism in the digital era. This article aims to examine the reinforcement of teacher professional ethics through educational unit policies in the digital era. The study employs a qualitative approach using library research by analyzing relevant literature sources. The findings indicate that educational unit policies play a strategic role in guiding teachers’ professional behavior, particularly in the use of digital technology, online communication, and student data protection. Effective implementation of these policies is supported by strengthening ethics-based digital literacy, teacher role modeling, and collaboration among schools, families, and communities. In addition, continuous monitoring and evaluation are crucial to ensure policy effectiveness. In conclusion, strengthening teacher professional ethics through adaptive, systematic, and sustainable policies can create an ethical, safe, and integrity-based educational environment in the digital era.